PENGARUH STATUS KARYAWAN, KOMPENSASI DAN FASILITAS KERJA TERHADAP KINERJA KARYAWAN - Dimas Bayu; Linda Khamelia; Anna Wulandari; Muhammad Sapruwan; Mardiyana (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2025)
This study aims to analyze the influence of employee status, compensation, and work facilities on employee performance at PT Astra Group. Employee performance is one of the important indicators of a company's success, so various factors that affect it need to be researched more deeply. The research method used is quantitative with a survey approach, involving a sample of employees working in several divisions of PT Astra Group. The results of the study show that the status of employees, whether permanent or contracted, has a significant effect on performance, where permanent employees tend to have better performance because of their sense of security in their work. The results of the study show that employee status has a significant influence on employee performance, where permanent employees tend to have a better level of performance than contract employees. Compensation provided by the company, both financial and non-financial, It also has a significant positive influence, where employees with fair and appropriate compensation feel more motivated to increase productivity. Work facilities, such as adequate infrastructure and a comfortable work environment, play an important role in creating optimal performance.